OSTEOMUSCULAR SYMPTOMS RELATED TO WORK IN PHYSIOTHERAPISTS: SYSTEMATIC REVIEW (Movimenta (ISSN 1984-4298), 2023)
Work-related musculoskeletal symptoms represent a public health problem, with costs for employers, employees, and health systems. Physical therapists can develop these symptoms due to the physical nature of the profession. The objective of this research was to verify the prevalence of work-related musculoskeletal symptoms in physical therapists and to relate sociodemographic and occupational aspects with these symptoms. Two independent researchers conducted searches in SciELO, PubMED, Web of Science, Scopus and PEDro databases. Articles that described work-related musculoskeletal symptoms in physical therapists, published from 2016 to 2020, in English, Portuguese or Spanish and that used the Nordic Musculoskeletal Questionnaire (NMQ) as an assessment instrument were included. Twelve articles were included in this review, all in English. The sample ranged from 42 to 986 physical therapists, aged between 21 and 73 years and most with an average between 30 and 40 years. When considering the articles that evaluated all body segments, most physical therapists presented work-related musculoskeletal symptoms in at least one body segment (78.1% to 96%). The most affected body segments were lumbar (32.3% to 66%) and cervical (36.3% to 63%) regions. Female professionals, with advanced age, with weekly workload greater than or equal to 40 hours, more time of practice, working in clinics, outpatient services and hospitals, present more musculoskeletal symptoms. It is concluded that physical therapists have a high prevalence of musculoskeletal symptoms, and that sociodemographic and occupational aspects influence these symptoms.
Keywords: Musculoskeletal pain; Musculoskeletal disorder; Physical Therapists.